Crítica constitucional a la categoría jurídica de ruralidad en España - Ana Torrecillas Martínez (Revista Vasca de Administración Pública)
The main objective of this work is to clarify the legal category of rurality in the Spanish legal system. The methodology employed is that of the legal sciences (legislative and doctrinal analysis), using as a basis the methodological premises of critical constitutionalism. A review is made of the constitutional legal framework, as well as of the state and autonomous legislation in development of the legal category of rurality, in order to finally highlight some key elements of the study. This research concludes, on the one hand, that it is advisable for regional legislators to adapt the state legal framework on rurality in their specific territories and, on the other hand, the need to pay attention to such regulation in order to offer complex and integral normative responses to the problematic situation of rural areas in Spain.